Perbandingan Sektor Potensial Perekonomian Kabupaten Tanah Bumbu: Analisis Input-Output Tahun 2010 dan 2016 - Zulkifli, Zulkifli; Muzdalifah, Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research aims to identify potential sectors based on linkage analysis, dispersion effect analysis, multiplier analysis and comparison of potential sectors in Tanah Bumbu Regency economy. It is quantitative research using Input-Output analysis with support IOW. Data used is from Badan Pusat Statistik of South Kalimantan Province and Badan Pusat Statistik of  Tanah Bumbu Regency. Forward linkage electricity, gases and fresh water sector, backward linkage construction shifted to manufacturing idustry sector. Disparsion effect electricity, gases and fresh water sector. Multiplier manufacturing industri sector. The results showed that 2010 and 2016 saw shifts in potential sectors Tanah Bumbu Regency economy.